Development of public health program for type 1 diabetes in a university community: preliminary evaluation of behavioural change wheel - Nwose, Ezekiel Uba; Digban, K A.; Anyasodor, A. E.; Bwititi, P. T.; Richards, R. S.; Igumbor, E. O. (Acta Biomedica Atenei Parmensis, 2017)
Background: Diabetes mellitus, including type 1 is a global public health problem among the young persons. While public health campaign and screening program is a potential strategy, but communication skills, knowledge and opinion of the healthcare personnel are indicated as variables that can impact patient’s education, which will lead to better outcome of care. Thus, in designing or planning a program for public health, workforce development considers opinion and behavioural change wheel of prospective personnel. Objective: The purpose of this preliminary study was to evaluate if a university academic department has the behavioural change wheel to function as workforce infrastructure for an envisioned program. Method: Survey of knowledge, attitude and practice (KAP) of a university community regarding diabetes type 1 was performed. The KAP were translated into behavioural change wheel comprising capacity, motivation and opportunity (CMO). Results: There are baseline indications of the behavioural change wheel potential of the public health department to run a T1D screening program. The number of participants who knew someone with T1D was significantly higher than the subgroup with no such knowledge (p<0.0004) and this improved when age factor is considered (p<0.00005). Conclusion: While the public health department of a university community has the behavioural change wheel or CMO to develop a workforce infrastructure for T1D screening program, the experience that comes with age of lecturers will be an important factor to enable such program to succeed.